1988
DOI: 10.1007/bf02571317
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between bone loss and increased bone turnover in ovariectomized rats

Abstract: To characterize osteopenic changes in ovariectomized (OVX) rats as a function of time, female Sprague Dawley rats (240 g body weight, 90 days old) were subjected to bilateral ovariectomy or sham surgery and killed at various times from 14-180 days postovariectomy. The proximal tibial metaphysis was processed undecalcified for quantitative bone histomorphometry. Osteopenia and increased indices of bone resorption and formation were detected in OVX rats as early as 14 days. Longitudinal bone growth was also sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
234
1
30

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(296 citation statements)
references
References 16 publications
31
234
1
30
Order By: Relevance
“…In accordance with previous findings [25], substantial trabecular bone loss occurred predominantly by a reduction of the number of trabeculae, and loss of trabecular connectivity density. Estrogen-deficient animals treated for 180 days with either an intravenous dose of risedronate or zoledronic acid had significantly higher trabecular bone volumes as compared with age-matched controls.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous findings [25], substantial trabecular bone loss occurred predominantly by a reduction of the number of trabeculae, and loss of trabecular connectivity density. Estrogen-deficient animals treated for 180 days with either an intravenous dose of risedronate or zoledronic acid had significantly higher trabecular bone volumes as compared with age-matched controls.…”
Section: Discussionsupporting
confidence: 92%
“…The first determinant depends on the availability of an animal model that mimics a human disease involving bone repair so that the data generated can be used to predict the drug efficacy and safety in patients. Examples of animal models with good predictability of clinical outcomes include models of postmenopausal osteoporosis [87][88][89][90][91][92], models of glucocorticoid induced bone loss [93][94][95][96], models of cancer metastasis to bone [97], disuse models [98,99], fracture healing models [100][101][102][103] and several others. The second determinant of successful experimentation relates to translational biomarkers of novel therapy efficacy and safety that can be accurately predicted and monitored in patients.…”
Section: Methods and Technologymentioning
confidence: 99%
“…Later, the same group has reported that, at different times from 14 to 180 days post-OVX performed on 90-day old rats, some, but not all, indices of bone formation rate already considered in the previous work differed between OVX and normal rats [39]. However, these conclusions are clouded with issues of correctness affecting the analysis of the data.…”
Section: Discussionmentioning
confidence: 94%
“…The current view for the response of rats to OVXinduced osteopenia relies largely on a few studies using histomorphometry analysis of static and dynamic parameters of bone turnover [37]. Since static parameters are not indicative of cellular activity and corresponding bone formation and resorption rates, the contrast with the accepted view will focus on the dynamic parameters which are more meaningful as indices of bone formation rate [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation